2005
DOI: 10.1097/01.mat.0000169115.56374.9f
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Anticoagulation and Prevention of Hemodialysis Catheter Malfunction

Abstract: Although chronic anticoagulation is commonly prescribed to prevent thrombosis and malfunction of hemodialysis tunneled cuffed catheters (TCC), there are only limited data regarding its efficacy. The aim of this prospective study was to evaluate whether anticoagulation with adjusted-dose warfarin targeting an international normalized ratio (INR) of 1.5-2.0 is associated with improved catheter outcome in long-term patients at high risk of TCC malfunction. Among the 65 patients included in the study, 35 were cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 14 publications
0
24
1
Order By: Relevance
“…However, HD patients have a higher risk of clotting. Arterio-venous graft and tunneled central venous catheter render an increased risk of local or systemic thromboembolism in HD patients [24][25][26]. Although the balance of risks and benefits of warfarin perform favorable in mild to moderate CKD patients with AF [19], as lack of evidence from randomized controlled trials in these populations, current and previous observational studies on warfarin therapy failed to offer recommendations regarding warfarin management.…”
Section: Discussionmentioning
confidence: 97%
“…However, HD patients have a higher risk of clotting. Arterio-venous graft and tunneled central venous catheter render an increased risk of local or systemic thromboembolism in HD patients [24][25][26]. Although the balance of risks and benefits of warfarin perform favorable in mild to moderate CKD patients with AF [19], as lack of evidence from randomized controlled trials in these populations, current and previous observational studies on warfarin therapy failed to offer recommendations regarding warfarin management.…”
Section: Discussionmentioning
confidence: 97%
“…Two studies evaluated low-intensity anticoagulation (target INR 1.4 to 1.9) for the prevention of HD access thrombosis (4,13). The one randomized, placebo-controlled trial was discontinued early because of a clinically important increase in major bleeding episodes in the patients who were randomly assigned to warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin (1 mg daily) was ineffective in a randomized trial of 85 patients, although there was a decrease in thrombosis in the subgroup that achieved INR greater than 1.0 (12). An observational study in which 35 patients with previous catheter malfunction were anticoagulated to INR 1.5 to 2.0 and compared with 35 controls showed a trend toward lower rates of malfunction in the anticoagulated patients, particularly in those in whom anticoagulation targets were met (13). A prospective observational study of 62 patients showed fewer episodes of thrombosis with warfarin (INR 2.0 to 3.0) compared with no therapy (14).…”
Section: Discussionmentioning
confidence: 99%